The importance of democratized resources in early-career training for bioimage analysts and bioimaging scientists - Laprade, Genevieve; Lee, Quinn; Gallik, Kristin L.; Nelson, Michael; Woo, Natalie; Terán Ramírez, Celina; Becerril Cuevas, Alexis Ricardo; Eliceiri, Kevin W.; Esquibel, Corinne (Frontiers in Bioinformatics, 2025)
The fields of bioimaging and image analysis are rapidly expanding as new technologies transform biological questions into novel insights. While professionals of varying expertise are essential to achieving these advancements, early-career scientists—a prominent user group within the imaging community—are often assumed to have the prerequisite knowledge and ability to use these tools. This demographic, consisting of students, post-docs, and bioimage analysis trainees, is critical for the field to continue to evolve and flourish. However, obstacles such as geographic location, language barriers, insufficient funding or training, and instrument availability hinder access to resources and introduce significant knowledge gaps, especially for scientists in early-career stages. Democratized resources for bioimaging and analysis such as forums, community organizations, and publicly available datasets have been helpful in overcoming barriers to access for early-career scientists. Here, we discuss the current tools and resources available for early-career researchers, highlight their limitations from the learners’ perspective, and propose strategies to better support this group. As bioimage analysis extends broadly into many scientific disciplines, we implore all members of this community, regardless of experience level, to empower next-generation scientists.